Fabrication and evaluation of oral tablets using natural mucoadhesive agent from seeds of Caesalpinia pulcherrima (L.) SW - Jeevanandham, S; Dhachinamoorthi, D; Senthil, V; Sekhar, K B Chandra (Asian Journal of Pharmaceutics (AJP), 2014)
Oral mucoadhesive sustained drug delivery systems of salbutamol sulfate were formulated using an isolated natural agent from the seeds of Caesalpinia pulcherrima. The isolated material was evaluated for various parameters, such as, melting point, viscosity, pH, elemental analysis, swelling index, phytochemical constituents, and solubility studies. The mucoadhesive characters of the isolated substance were identified by a comparative study with hydroxyl propyl cellulose and sodium alginate, by various in vitro methods, such as, Shear stress measurement,Wilhelmy’s method, Falling sphere method, and Detachment force measurement. Formulation and evaluation of mucoadhesive oral tablets of salbutamol sulfate (100 mg), using isolated natural materials in different proportions, and in vitro release studies, were carried out for three different formulations according to the U.S.P apparatus two (paddle method). Each 100 mg tablet was taken in 900 ml of acid buffer 1.2 and maintained at 37 ÌŠC. After two hours the filtrate was collected and replaced in buffer 7.4. In vitro releases of three different formulations for nine hours were studied, which showed the sustained action of drug release with increasing the concentration of the isolated natural mucoadhesive agent in the formulations.